FORMULASI LOTION EKSTRAK TERPURIFIKASI DAUN KENIKIR (Cosmos caudatus Kunth). - Erwan Kurnianto; Ika Ristia Rahman; Dian Kartikasari; Hairunnisa Hairunnisa (Jurnal Insan Farmasi Indonesia, 2021)
Kenikir leaves (Cosmos caudatus Kunth) is a plant that is used as a vegetable and ornamental plant. Kenikirleaves contain flavonoid, phenol, diterpene, and ascorbic acid phytochemicals. The phytochemical content of kenikir leaves has antioxidant activity. The preparation widely used in applying antioxidants is lotion because of its easy use. This study aims to formulate a lotion from the purified extract of kenikir leaves by varying the extract 0.1%, 0.25% and 0.5%. The lotion base used was VCO, Tween 80, PEG 400, Aquadest. The physical characteristics evaluated were organoleptic, homogeneity, pH, spreadability, and emulsion type. From the results test, purified extract lotion of kenikir leaves gave a green color, characteristic smell of the extract, homogeneous, pH value according to lotion requirements, dispersion according to the standard range of 5-7cm, emulsion type of lotion oil in water.